SIGNAL FUNCTIONS OF HORMONES AND RESPONSE TO POLLEN EMBRYOGENESIS INDUCTION STRESSORS - Bekkuzhina, S.S.; Borovikov, S.N.; Rahimbaev, I. (Eurasian Journal of Applied Biotechnology, 2014)
The Article presents the world publications review on theoretical and applied aspects of haploid technologies, in particular the ways to increase pollen embryogenesis efficiency. The analytical review discusses in details the issues of donor plants hormonal pretreatment role in induction of microspore sporophytic development pattern. Phytohormone balance is one of the key mechanisms of microspores shifting from gametophytic to sporophytic development pattern. In addition, the Article specifies the impact of various stressors on microspore reprogramming from gametophytic to sporophytic development pattern. In discussing this issue all plant pretreatments being in use are distributed into new and old pretreatment methods before in vitro introduction.The result of our experimental research is to create an effective biological system , that allows switching development of microspores from the gametophytic type to the sporophytic development type based on pretreatment of cut plants hormone of auxin cut type as - IAA, and 2,4-D with contents of endogenous IAA in plants. The developed method improves the efficiency of pollen embryogenesis to 8%. Conventional methods of pretreatment are that hormonal induction factor is added to the environment, and plants cut were subjected while pre-treatment in our experiments.